CODE MIXING IN TV SHOW ENTITLED HIJAB TRAVELING ON TRANS7 - Sri Arfani; Nafiah Mahmudah (STIBA IEC JAKARTA, 2020)
Code mixing can occur anywhere. Mixed code is a mixture of two or more languages. Code mixing occurs when a speaker using a language dominantly supports a speech inserted with other language elements. This paper is conducted to get data about code mixing, especially in delivered by the presenter in the Hijab Traveling in Trans7 television program. The research used descriptive qualitative research. The data were collected from utterances delivered by the presenter in the Hijab Traveling in Trans7 television program. Process of analyzing the types of mixed code the writer used Suwito's theory. The results are 15 data found which the writer has classified into linguistic elements include the insertion of words, phrases, clauses, repetition of words, and idiom. Proses of analyzing the causes of mixed code the writer used the theory of Basir. The results are found 9 data. The result indicated that presenters on the Hijab Traveling in Trans7 television program often intervene in code. Based on all the analysis of data the writer can conclude that the sentences uttered by the presenter of Hijab Traveling in Trans7 television program prove that presenter often use mixed codes because the presenter can speak more than one language and the presenter has extensive knowledge.